The handbook of logistics and distribution management understanding the supply chain - Rushton, Alan; Croucher, Phil 1954-; Baker, Peter 1950- (Kogan Page, 2022)
"Fully grasp the core principles of logistics, distribution management and the supply chain, in addition to emerging trends and the latest technologies, with this definitive guide that offers clear and straightforward explanations. The Handbook of Logistics and Distribution Management provides students with a complete overview of all aspects of setting up, managing, and optimizing supply chains. Written by an author team with years of practical experience in some of the most challenging environments across the world, this textbook is underpinned by real-world data and worked examples throughout. Designed to offer a complete understanding of how supply chains fit together, The Handbook of Logistics and Distribution is structured logically and delves into topics in more detail than collections of research papers of miscellaneous works. With coverage on all the key aspects of distribution, logistics and supply chain management, students will find this to be an invaluable resource and useful desk reference throughout their careers. The seventh edition includes updates and solutions designed to meet the challenges faced by those studying and working in the sector. New material covers future technologies, including artificial intelligence, cyber-security, 5G mobile networks, drones and cobots, and how these can be used to optimize operations and increase productivity. Online resources include lecture slides (tables, images and formulae from the text), glossary of terms, weblinks, blog articles, video interviews and infographics"--